A comparative study of lyophilized bovine pericardium and tunica parietalis vaginalis for repair of large abdominal wall defects in a rabbit model - Ayele, Taddese; Abu Bakar @ Zakaria, Md Zuki; Mohammed Alitheen, Noorjahan Banu; Mohamed Mustapha, Noordin (Academic Journals, 2011)
The aim of this study is to investigate the effectiveness of lyophilized bovine pericardium and tunica vaginalis in repairing large abdominal wall defect in a rabbit model. Full thickness (all the layers of muscles except the skin) abdominal wall defects (3 x 4 cm) were created in 18 anaesthetized male clinically healthy New Zealand white rabbits and randomly divided into two equal group (n= 9 each). The defects of the first group were repaired with bovine pericardium, whereas the second group was with bovine tunica vaginalis parietalis. Three animals were sacrificed at 7th, 14th and 30th days of postimplantation from each group and the explanted specimens were subjected to macroscopic and microscopic examinations. The explanted grafts were replaced by newly formed collagen fibres and neo-vascularisation without any infection as well as formation of seroma. The cellular reaction was almost similar in each group. Therefore, these scaffolds can provide a structural replacement for severe and large abdominal wall defects.